THE RELATIONSHIP BETWEEN IMMIGRATION POLICIES AND THEIR INFLUENCE ON SOCIAL COHESION AND POLITICAL STABILITY IN NIGERIA - Toye Manuwa (International Studies Journal)
This study examines the relationship between immigration policies and their influence on social cohesion and political stability in Nigeria. It analyzes the historical and contemporary patterns of immigration in Nigeria, as well as the legal and institutional frameworks that regulate them. It also explores the socio-economic and political impacts of immigration on the host communities and the immigrants themselves. The study argues that immigration policies in Nigeria have been largely reactive, restrictive and ineffective, failing to address the root causes and consequences of migration. The study further contends that immigration policies have contributed to social fragmentation, ethnic polarization, political violence and insecurity in Nigeria, undermining the prospects of national integration and development. The study recommends a comprehensive and holistic approach to migration management that balances the rights and interests of all stakeholders, promotes regional and international cooperation, and fosters social cohesion and political stability in Nigeria.